2017
DOI: 10.1165/rcmb.2016-0306oc
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rho-Associated Coiled-Coil Forming Kinase Isoforms in Regulation of Stiffness-Induced Myofibroblast Differentiation in Lung Fibrosis

Abstract: Fibrosis is a major cause of progressive organ dysfunction in several chronic pulmonary diseases. Rho-associated coiled-coil forming kinase (ROCK) has been shown to be involved in myofibroblast differentiation driven by altered matrix stiffness in a fibrotic state. There are two known ROCK isoforms in humans, ROCK1 and ROCK2, but the specific role of each isoform in myofibroblast differentiation in lung fibrosis remains unknown. To study this, we developed a gelatin methacryloyl hydrogel-based culture system w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…ROCK1 and ROCK2 are downstream signals of RhoA and are reported to be involved in the mechanotransduction pathway. 59 This study focused mainly on the role of ROCK2, as ROCK2 had greater expression than ROCK1 in the eye. 19 Further studies are needed to explore whether ROCK1 has a role in myopia sclera remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…ROCK1 and ROCK2 are downstream signals of RhoA and are reported to be involved in the mechanotransduction pathway. 59 This study focused mainly on the role of ROCK2, as ROCK2 had greater expression than ROCK1 in the eye. 19 Further studies are needed to explore whether ROCK1 has a role in myopia sclera remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained from animal models indicate that Rho-kinase has a main role in the pathophysiology of asthma [ 20 23 ]. A previous study demonstrated that challenge with OVA can induce Rho-kinase activation [ 23 ] that is associated with increased collagen synthesis [ 47 ], α-SMA expression and fiber assembly, F-actin polymerization [ 48 ] and myosin filament assembly in myofibroblasts [ 49 ]. We found that the inhibition of Rho-kinase decreases AHR and airway remodeling in asthmatic animal.…”
Section: Discussionmentioning
confidence: 99%
“…ROCK is the major downstream effector of Rho that drives cell contractility and is a mediator of fibrotic pathologies (93,107). ROCK phosphorylates myosin light chain and myosin light chain phosphatase to induce the generation of cellular force from actomyosin filament contraction.…”
Section: Rho-associated Kinasementioning
confidence: 99%
“…ROCK phosphorylates myosin light chain and myosin light chain phosphatase to induce the generation of cellular force from actomyosin filament contraction. Recently, a stiffness-dependent role for ROCK in driving fibroblast to myofibroblast conversion in pulmonary fibrosis was identified, and ROCK inhibition attenuated increased endothelial permeability caused by age-related increased intima stiffness (107,108). ROCK inhibition can be pursued using traditional small-molecule discovery efforts but is also plagued by nonspecificity.…”
Section: Rho-associated Kinasementioning
confidence: 99%